PERBANYAKAN DAN PENYIMPANAN KULTUR SAMBUNG NYAWA [Gynura procumbens (Lour.) Merr.] DENGAN TEKNIK IN-VITRO - Djadja Siti Hazar Hoesen (BERITA BIOLOGI, 2001)
Sambung nyawa [Gynura procumbens(Lour.)Merr.]is one of the traditional medicine sources.The plants are not cultivated intensively in the field. One of the efforts to maintain and to propagate this species is by multiplication through tissue culture method. Nodes explants were cultured in MS normal and half strength concentration macroelements, supplemented with microelements and vitamins; combination of cytokinin BA (2 mg/1), thidiazuron (0.01 mg/1 and 0.1 mg/1) and adenine sulphate (5 mg/1).Auxin (2,4D 0.5 mg/1) in combination were added in media as treatments and activated charcoal (2 g/1) as antioxidant. Young leaves explants were also cultured in the same basic medium (MS and 'A MS) in treatments with cytokinin (BA and thidiazuron).The results from nodes and young leaves explant indicated that the highest number of survival cultures were obtained from combination between BA (2 mg/1) and thidiazuron (0.01 mg/1) in MS normal strength basic medium.In acclimatization stage, 100% of plantlets survived and successfully transplanted to soil medium in the field; maintenance study indicated that subculture was prolonged until 52 weeks.